2023
DOI: 10.1002/jmv.28419
|View full text |Cite
|
Sign up to set email alerts
|

Omicron infection increases IgG binding to spike protein of predecessor variants

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission in India in 2020-2022 was driven predominantly by Wild (Wuhan-Hu-1 and D614G), Delta, and Omicron variants. The aim of this study was to examine the effect of infections on the humoral immune response and cross-reactivity to spike proteins of Wuhan-Hu-1, Delta, C.1.2., and Omicron. Residual archival sera (N = 81) received between January 2020 and March 2022 were included. Infection status was inferred by a positive SARS-CoV-2 RT-PCR and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
(116 reference statements)
0
5
0
2
Order By: Relevance
“…Recent studies (11)(12)(13)(14) have observed a limited variant-specific cross-neutralizing immunity after Omicron breakthrough infection. In line with our data, we suggest that Omicron breakthrough infections are less immunogenic than, for example, Delta, thus providing reduced protection against reinfection or infection from future variants.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (11)(12)(13)(14) have observed a limited variant-specific cross-neutralizing immunity after Omicron breakthrough infection. In line with our data, we suggest that Omicron breakthrough infections are less immunogenic than, for example, Delta, thus providing reduced protection against reinfection or infection from future variants.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to evaluate variant-specific immunization is to compare serum samples from patients who had a prior infection with different SARS-CoV-2 variants in terms of their cross-reactivity. However, only a few detailed reports on this subject have been published [ 8 , 9 ]. In particular, it was demonstrated that Omicron infections lead to increased antibody binding to pre-Omicron S variants [ 9 ]; at the same time, sera from the Delta and pre-Delta periods were similar in binding to S protein variants.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few detailed reports on this subject have been published [ 8 , 9 ]. In particular, it was demonstrated that Omicron infections lead to increased antibody binding to pre-Omicron S variants [ 9 ]; at the same time, sera from the Delta and pre-Delta periods were similar in binding to S protein variants. In order to compare more comprehensively the humoral immunity in patients from the D614G and Delta periods, we used a set of methods, both standard (ELISA, pVNA, and sVNA) and especially designed for this case (fcVNA and mELISA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Memory B cells formed in response to primary and secondary vaccination with S from an ancestral SARS-CoV-2 strain tend to be preferentially restimulated by a third boosting immunization with Omicron BA.1 S in a process termed antigen imprinting 83 - 85 . This is due to memory B cells preferentially recognizing S epitopes in BA.1 shared with the vaccine strain and results in antibodies that are relatively ineffective in neutralizing BA.1 84 , 85 . However, small numbers of B cells recognizing novel epitopes present in BA.1 that were not present in ancestral S were also stimulated on immunizing with BA.1 S 83 .…”
Section: Sars-cov-2 Variants Arising After Widespread Community Infec...mentioning
confidence: 99%